DISPERSION MODELING OF ATMOSPHERIC EMISSIONS OF PARTICULATE MATTER (PM10) AND EVALUATION OF THE CONTRIBUTION OF DIFFERENT SOURCES OF AIR POLLUTION IN THE TOWN OF SVISHTOV, BULGARIA: DISPERSION MODELING OF ATMOSPHERIC EMISSIONS OF PARTICULATE MATTER (PM10) AND EVALUATION OF THE CONTRIBUTION OF DIFFERENT SOURCES OF AIR POLLUTION IN THE TOWN OF SVISHTOV, BULGARIA - Vlaknenski, Tsenislav; Stoychev, Pencho; Chuturkova, Rozalina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
This dispersion model and assessment of air pollution with particulate matter (PM10) in the town of Svishtov, Bulgaria are developed in accordance with the requirements of Bulgarian legislation and the Framework Directive 96/62/EC on the assessment and control of the Atmospheric Air Quality. Based on an assessment of sources of air pollution in the town of Svishtov, Bulgaria are classified input data for the model including point, area and line sources of PM10. Quantitative results of modeling of the main sources of PM10 and background air pollution of Svishtov for 2007- 2010 confirm that local ambient pollution and emissions of PM10 from residential heating is a key contributor to atmospheric pollution in the city.